Restrictions and satisfaction with participation in patients who are ADL-independent after an aneurysmal subarachnoid hemorrhage. Issue 2 (17th February 2017) - Huenges Wajer, Irene M. C.; Visser-Meily, Johanna M. A.; Greebe, Paut; Post, Marcel W. M.; Rinkel, Gabriel J. E.; van Zandvoort, Martine J. E.
Abstract : Background : Most survivors of an aneurysmal subarachnoid hemorrhage (aSAH) are ADL-independent, but they often experience restrictions in (social) activities and, therefore, cannot regain their pre-morbid level of participation. Objective : In this study, participation restrictions and participation satisfaction experienced after aSAH were assessed. Moreover, possible predictors of participation after aSAH were examined to identify goals for rehabilitation. Method : Participation restrictions experienced by a series of 67 patients visiting our SAH outpatient clinic were assessed as part of standard clinical care using the Participation Restrictions and Satisfaction sections of the Utrecht Scale for Evaluation of Rehabilitation Participation (USER-Participation) 6 months after aSAH . Cognitive impairments, cognitive and emotional complaints, and symptoms of depression and anxiety, assessed 10 weeks after aSAH, were examined as possible predictors of participation by means of linear regression analysis. Results : Although patients were ADL-independent, 64% reported one or more participation restrictions and 60% were dissatisfied in one or more participation domains. Most commonly experienced restrictions concerned housekeeping, chores in and around the house, and physical exercise. Dissatisfaction was most often reported about outdoor activities, mobility, and work/housekeeping. The main predictors of participation restrictions as well as satisfaction with participation were cognitive complaints (subjective) ( β  = −.30, p  = .03 and β  = −.40, p  = .002, respectively) and anxiety ( β  = .32, p  = .02 and β  = −.34, p  = .007, respectively). Conclusions : Almost two-thirds of the ADL-independent patients experienced problems of participation 6 months after aSAH. Cognitive complaints (subjective) and anxiety symptoms showed the strongest association with participation restrictions and satisfaction. Cognitive rehabilitation and anxiety-reducing interventions may help to optimize rehabilitation and increase participation after aSAH.